Pendekatan Pembelajaran Kontekstual Pada Kemampuan Berpikir Tingkat Tinggi Siswa Di SMP Adabiyah Palembang (Universitas Muhammadiyah Palembang, 2022)
This research purposed to determine the effect contextual teaching and learning approach toward the higher order thinking skills of mathematics student at SMP A Palembang. Types of research was quantitative with True Experimental Design categories posttest-only control design. The population was all class VII in School 2019/2020 academic year consists of six classes. The sample in this research taken by using simple random sampling. From six classes of the population of samples that classes are VII5 as an experiment class and classes are VII6 as a control class with 32 stdents by classes. Conduct research each four times meeting, the first, second and third meeting for learning and the fourth meeting for post-test. Research data collected through test higher order thingking skills and observation contextual teaching and learning. The data obtained from the test are used to test the research hypothesis by using Independent Sample t Test SPSS 21. Statstical calculations obtained from the test result generate sig (2-tailed) = 0,000 < ? (0,05) that causes Ho rejected and Ha accepted. Therefore, it could be concluded that there was an effect of contextual teaching and learning approach on higher order thinking skills of mathematics student at Senior High School Palembang.